Is there Unity in Europe? First Survey of EUPSA Delegates on the Management of Gastroschisis - Zani, Augusto; Ruttenstock, Elke; Davenport, Mark; Ade-Ajayi, Niyi (European Journal of Pediatric Surgery, 2013)
Aim To report the first European survey on the current management of gastroschisis and ascertain the degree of variability between centers.Methods A 10-question survey was administered at the 2011 European Paediatric Surgeons' Association (EUPSA) Congress. Questionnaires were completed by 205 delegates from 39 countries. A total of 21 responses (10%) were incomplete and voided. The remaining 184 were divided on the basis of following region of practice: Western Europe (WE, n = 102), Eastern Europe (EE, n = 59), and non-European countries (n = 23). Differences between WE and EE were analyzed using contingency tests. p < 0.05 was considered significant.Results A total of 15% WE and 2% EE responders work in centers where antenatal magnetic resonance imaging scans are routinely used. Nonplanned delivery is the most popular approach (WE 46%, EE 58%). Primary closure is the preferred choice (WE 92%, EE 86%), and it is achieved by operative fascial closure in the majority (WE 80%, EE 75%) rather than by Bianchi technique (WE 20%, EE 25%). Staged reduction and closure is less popular (WE 8%, EE 14%), and it is achieved by custom-made silo (WE 25%, EE 12.5%), preformed silo (PFS) followed by surgical closure (WE 63%, EE 75%), or PFS followed by sutureless closure (WE 12%, EE 12.5%). Objection to PFS in WE is mainly related to surgeons' lack of confidence in the technique (40%), whereas in EE it is due to unavailability and high cost (62%, p = 0.01). In case of associated intestinal atresia, immediate resection and anastomosis is preferred by 60% of WE surgeons versus 35% of EE surgeons (p = 0.03), who equally favor primary closure and delayed surgery (33%). Nutrition is preferably delivered by peripheral long line in WE (64%) and by central line inserted in the first week of life in EE (62%, p = 0.003).Conclusions Primary fascial closure is currently the preferred method of gastroschisis closure across Europe. Aspects of care such as strategy for intestinal atresia and delivery of parenteral nutrition differ significantly between WE and EE. Economic considerations appear to influence management strategy particularly in EE. A Europe-wide audit appears warranted to identify whether this survey reflects actual practice.
Keywords: abdominal wall defect; preformed silo; intestinal atresia; Bianchi